Pengaruh Budaya Organisasi Dan Kepemimpinan Terhadap Kinerja Karyawan Dimediasi Semangat Kerja Pada Riau Fiber Head Office PT Riau Andalan Pulp And Paper - Hidayat, Fitra; Hendriani, Susi; Kamaliah (Bahtera Inovasi, 2024)
Performance contains components of competence and productivity results, so performance results are highly dependent on the level of individual ability in achieving them, especially organizational goals. Performance emphasizes the results of the functions of a job or what comes out (out-come). If you pay further attention to what happens in a job or position is a process that processes input into output (work results). This study aims to Organizational Culture and Leadership on Morale. Effect of Organizational Culture and Leadership on Employee Performance. The effect of Work Morale on Employee Performance. The influence of Organizational Culture on Employee Performance through Employee Morale and the influence of Leadership on Employee Performance through Morale.  In this study, the population was 100 employees of the Head Office of the Riaufiber Division of PT RAPP. The data used in this study are primary data and secondary data, while the data collection technique uses a questionnaire. The data analysis technique used in this study is sem. From the results of the study it was found that organizational culture and leadership affect morale and performance. Morale has a significant effect on employee performance. Organizational culture has a significant effect on employee performance through morale. Leadership has a significant effect on employee performance through morale.